Association between gestational depression and weight management behaviors during pregnancy: A cross-sectional study in Eastern China - Shiqi Zhao; Xueqing Peng; Hua Zhou; Jinjin Ge; Meng Zhou; Anita Nyarkoa Walker; Hua You; Hua You (Frontiers Media S.A., 2022)
An undesirable psychological state may deteriorate individual's weight management-related behaviors. This study aims to see if ineffective weight control measures were linked to depressive symptoms during pregnancy. We conducted a cross-sectional questionnaire survey of 784 pregnant women and collected information on sociodemographic factors, maternal characteristics, depression, and weight management activities throughout pregnancy (exercise management, dietary management, self-monitoring regulation, and management objectives). About 17.5% of pregnant women exhibited depressive symptoms. The mean score on dietary management was upper-middle, exercise management and self-monitoring regulation were medium, and management objectives were lower-middle. Multivariable linear regression analysis revealed that pregnant women with depressive symptoms had lower levels of exercise management (β = −1.585, p = 0.005), dietary management (adjusted β = −0.984, p = 0.002), and management objectives (adjusted β = −0.726, p = 0.009). However, there was no significant relationship between depressive symptoms and pregnant women's self-monitoring regulating behavior (p > 0.05). The findings indicated the inverse association between depressive symptoms and gestational weight management behaviors. These results offer important indications for pregnancy weight management professionals by highlighting the need for mental health interventions for pregnant women experiencing depressive symptoms.